PELAKSANAAN PERKAWINAN DI BAWAH UMUR PADA MASYARAKAT ADAT TALANG MAMAK DESA TALANG PERIGI KECAMATAN RAKIT KULIM KABUPATEN INDRAGIRI HULU - Lestari, Rafida; Ismi, Hayatul; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Talang Mamak is also called Orang Adat, Langkat Lama or Talang. The title of Talang means a person who lives in remote areas and is alienated in the forest. The pattern of settlements scattered, generally located on the left side of the river with a small number of households or huts. Talang Mamak customary tribe located in the District of Rakit Kulim one of them located in Talang Perigi Village is a group dependent on the existence of nature. They use forests for medicinal materials, forest plants are also used for living equipment, such as woody species, bark, leaves, sap, rattan, and bamboo.Childrens life Talang Mamak tribe who live in Talang Perigi village generally do not have education because they do not have birth certificate and so and because these indigenous peoples do not see the future and do not attach any importance to it then thats the children of indigenous tribe Talang Mamak many do not hold education. Talang Mamak indigenous peoples in Talang Perigi Village generally adhere to Islam, but in marriage they put forward the marriage based on their customary belief.The purpose of writing this thesis, namely; First, To know the implementation of underage marriage on indigenous peoples Talang Mamak Tribe in Talang Perigi Village, Rakit Kulim Sub-district Indragiri Hulu Regency, Secondly, To know the factors of underage marriage in Indigenous people of Talang Mamak Tribe in Talang Perigi Village Rakit Kulim Kabupaten Indragiri Hulu.This type of research is a sociological research, because the author of the study of the effectiveness of the current law. This research was conducted in Indigenous Peoples Talang Mamak Indragiri Hulu, while the population and sample were all parties related to the problem studied in this research, data source used, primary data, secondary data and tertiary data, data collection technique in this research with interviews, questionnaires and literature study.From the results of research problems there are two main things that can be concluded. First, Customary Law does not recognize the age limit of immature and adult. Secondly, the law is applied if there are children who have problems due to marriage under age. In addition also from the point of moral norms due to the law, many people who will criticize for marriage underage. Suggestion of the writer, First, the public should not be influenced by the prevailing customs and traditions. Secondly, the Government by revising Law Number 1 Year 1974 The support and demand for the revision of the Marriage Law is a manifestation of a joint effort to save the ahead of Indonesian children.Keywords: Marriage - Under Age - Indigenous Peoples - Talang Mamak